The impact of perioperative fluid therapy on short-term outcomes and 5-year survival among patients undergoing colorectal cancer surgery – A prospective cohort study within an ERAS protocol. Issue 8 (August 2017) - Asklid, D.; Segelman, J.; Gedda, C.; Hjern, F.; Pekkari, K.; Gustafsson, U.O.
Abstract: Background: Restricted perioperative fluid therapy is one of several interventions in the enhanced recovery after surgery (ERAS) protocol, designed to reduce morbidity and hospital stay after surgery. The impact of this single intervention on short and long term outcome after colorectal surgery is unknown. Patients and methods: This cohort study includes all consecutive patients operated with abdominal resection of colorectal cancer 2002–2007 at Ersta Hospital, Stockholm, Sweden. All patients were treated within an ERAS protocol and registered in the ERAS-database. Compliance to interventions in the ERAS protocol was analysed. The impact of a restrictive perioperative fluid therapy (≤3000 ml on the day of surgery) protocol on short-term outcomes as well as 5-year survival was assessed with multivariable analysis adjusted for confounding factors. Results: Nine hundred and eleven patients were included. Patients receiving ≤3000 ml of intravenous fluids on the day of surgery had a lower risk of complications OR 0.44 (95% C I 0.28–0.71), symptoms delaying discharge OR 0.47(95% C I 0.32–0.70) and shorter length of stay compared with patients receiving >3000 ml. In cox regression analysis, the risk of cancer specific death was reduced with 55% HR 0.45(95% C I 0.25–0.81) for patients receiving ≤ 3000 ml compared with patients receiving >3000 ml. Conclusion: A restrictive compared with a non-restrictive perioperative fluid therapy on the day of surgery may be associated with lower short-term complication rates, faster recovery, shorter length of stay and improved 5-year survival.